Immune reconstitution inflammatory syndrome associated with pulmonary sarcoidosis in an HIV-infected patient: an immunohistochemical study - Miranda,Érique José Peixoto de (2011)
Sarcoidosis has been rarely described in literature as a cause of interstitial pulmonary disease associated with AIDS. This study reports a case of immune reconstitution inflammatory syndrome associated with pulmonary sarcoidosis in a patient with a history of previous pulmonary tuberculosis concomitant with HIV infection. Results of the immunohistochemical study of samples from the resected right lower lobe are described. Pathological findings suggest a role of Th1, Th2 and Th17 response in IRIS associated sarcoidosis.